Medicinal Tree Diversity in Different Agroforestry Systems in South India - Patil, S.V.; Depommier, D. (Indian Journal of Agroforestry, 2020)
Many plants grown in traditional agricultural systems in India have medicinal value. These are found in home gardens, as scattered trees in croplands and on field risers. The current tree planting methods; characterization of species diversity in managed ecosystems and appraisal of the multiplicity of products and services in different agro ecosystems were studied. The French Institute of Pondicherry has been developed a "Multipurpose tree database for Agroforestry Research and Appropriate Management (MARAM)" under the program on usage of biodiversity and ecosystems modified by human activity in South India. The MARAM database contains, 269 tree species encountered in the 544 farms sampled over 61 districts and six AEZs of three South Indian states viz., Karnataka, Kerala and Tamil Nadu. All these species, which are reported by the land holders, are broadly classified by nine major uses. Though 200 of these species are reported in literature as having medicinal use, the landowners in our study area consider only 85 species to be of medicinal use, 8 of which are endemic to the Western Ghats and 27 are exotic species. Indeed, 58 indigenous species are regenerated naturally in the farmland and the landowners exploit these species for their valuable products and for medicinal uses.